Cytoreductive surgery and ovarian carcinoma - Balbi, G.; Monteverde, A.; Landino, I.; Amparo Manganaro, et al., M. (Acta Biomedica Atenei Parmensis, 2009)
Purpose of investigation: the aim of this study is to demonstrate if Cytoreductive surgery in patients with ovarian carcinoma increases overall survival. Methods: during the period between 1998 and 2008, 60 patients with a relapse of ovarian cancer, were evaluated in order to undergo a cytoreductive surgery. Results: an optimal cytoreduction (residual disease 12 months is the best predictive factor of improved survival rate after surgery.